THE DEVELOPMENT OF PROFESSIONAL FLIP PDF BASED LEARNING MEDIA IN THEMATIC LEARNING AT THE THIRD GRADE STUDENTS OF ELEMENTARY SCHOOL - Siti Fatonah; Teguh Yunianto (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract:Thematic learning requires teachers' creativity in selecting and developing learning media; one of them is by using professional flip pdf learning media. This study aimed to determine the feasibility and investigate teachers' and students' responses towards professional flip pdf for thematic learning with the 'loving plants and animals' theme. This research used Research and Development method with Borg and Gall model. The data collecting procedures were through observation, interview, and documentation. The results indicated that The development of learning media professional flip pdf gained 94.54% from media experts with the very feasible category, material experts 86.66% with the very feasible category, and linguists 94.54% with a very feasible category. In addition, the average of teachers' response obtained was 95% with the very feasible category. The small-scale trial was 91.3%, and the large-scale trial was obtained 95.8%, both with very attractive interpretation criteria. Therefore, professional pdf flip-based learning media are very feasible and very interesting to be used as thematic learning media.Abstrak:Pembelajaran tematik membutuhkan kreativitas guru dalam memilih dan mengembangkan media pembelajaran; salah satunya dengan menggunakan media pembelajaran flip pdf professional. Penelitian ini bertujuan untuk mengetahui kelayakan, respon guru dan siswa terhadap flip pdf profesional untuk pembelajaran tematik dengan tema 'menyayangi tumbuhan dan binatang'. Penelitian ini menggunakan metode Research and Development dengan model Borg and Gall. Teknik pengumpulan data dalam penelitian menggunakan observasi, wawancara, angket dan dokumentasi. Hasil penelitian menunjukkan bahwa pengembangan media pembelajaran flip pdf profesional diperoleh rata-rata 94,54% dari ahli media dengan kategori sangat layak, ahli materi 86,66% dengan kategori sangat layak, dan ahli bahasa 94,54% dengan kategori sangat layak. Selain itu, rata-rata respon guru yang diperoleh adalah 95% dengan kategori sangat layak. Uji coba skala kecil sebesar 91,3% dan uji coba skala besar diperoleh 95,8%, keduanya mendapat kriteria interpretasi sangat menarik. Denga demikian, media pembelajaran berbasis flip pdf profesional sangat layak dan sangat menarik untuk digunakan sebagai media pembelajaran tematik.